Educational technologies for the prevention of child obesity: Integrative literature review (Research, Society and Development, 2022)
Objective: To identify educational technologies for the prevention of childhood obesity, according to studies found in the scientific literature. Method: Integrative review carried out in the following databases: Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), SCOPUS, National Library of Medicine and National Institutes of Health (MEDLINE/PubMed), in the period from August to November 2019. To define the information extracted and obtain data from all the articles that were selected in the database search, a data collection form was prepared. Results: After the selection process of articles based on the established inclusion criteria, 10 articles were chosen to compose this review. The most cited educational technologies were virtual and printed. Conclusion: The educational technologies analyzed are important tools in the prevention of childhood obesity, promoting changes in habits, preventing diseases, providing an improvement in health and quality of life. However, there are few studies addressing this issue.